2020
DOI: 10.1111/mmi.14465
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide as a developmental and metabolic signal in filamentous fungi

Abstract: The short‐lived hydrophobic gas nitric oxide (NO) is a broadly conserved signaling molecule in all domains of life, including the ubiquitous and versatile filamentous fungi (molds). Several studies have suggested that NO plays a vast and diverse signaling role in molds. In this review, we summarize NO‐mediated signaling and the biosynthesis and degradation of NO in molds, and highlight the recent advances in understanding the NO‐mediated regulation of morphological and physiological processes throughout the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 87 publications
3
37
0
Order By: Relevance
“…Several studies have reported that sporulation in lamentous fungi is promoted by application of external NO but inhibited by sGC inhibitor L-NAME or ODQ. However, sporulation can be restored by exogenous cGMP (Zhao et al 2020). In our study, NO promoted formation of conidia and pseudothecia, and melanin production can also be compromised by sGC speci c inhibitor NS-2080 even in the presence of SNP.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…Several studies have reported that sporulation in lamentous fungi is promoted by application of external NO but inhibited by sGC inhibitor L-NAME or ODQ. However, sporulation can be restored by exogenous cGMP (Zhao et al 2020). In our study, NO promoted formation of conidia and pseudothecia, and melanin production can also be compromised by sGC speci c inhibitor NS-2080 even in the presence of SNP.…”
Section: Discussionsupporting
confidence: 45%
“…Cellular NO levels also affect sexual development in lamentous fungi (reviewed by Zhao et al 2020). In Aspergillus nidulans, the increase in cellular NO levels by disrupting the genes encoding avohemoglobin or supplementing NO-releasing compound promotes the formation of cleistothecia (Baidya et a., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fungi, NO is synthesized through a reductive denitrification pathway from nitrite, and through an oxidative pathway from L-arginine, although the detailed biochemical mechanisms have not yet been fully elucidated (11)(12)(13). Compared to mammals, plants, and bacteria, the role of NO in fungal biology is understudied.…”
Section: Significancementioning
confidence: 99%